PENGURANGAN PEMBOROSAN BERAT BERLEBIH BISKUIT X MENGGUNAKAN METODE LEAN SIX SIGMA PT XYZ - Bayu Prasetya, Andika
PT XYZ is grappled by waste problems due to overweight loss in production line 1. Overweight loss happened when the slug of RC biscuits is weighted at the ebd and recorded to have weight above the Upper Specification Limit (USL), overweight loss is the biggest material loss component in PT XYZ. The effort to reduce overweight loss in production line 1 is done by the guiding principles of lean and six sigma. The tools of lean and six sigma are often used by industry practitioners to solve problem related to waste and to increase process capability. The tools used in this research are determination of critical to quality (CtQ) characteristics, process mapping, design of experiments (DoE), and the formulation of the solutions to be applied on the later stages of this research. The processes in production line 1 which are the main focus are the forming, baking, and packaging process. The CtQs are the specifications that determine the uniformity of shape and weight of the biscuit they are; dough weight, basecake weight, biscuit weight, biscuit thickness, and biscuit diameter. The aim of DoE is to optimize three variables of process that influence the shape uniformity of biscuits, these variables are; ammonium bicarbonate used in mixing process and the machinery parameters in the forming process these parameters are gauge roll 3 thickness settings and moulder (rotary cutter) conveyor velocity. The improvements done in this research are upgrades on rotary cutter conveyor and rotary cutter mechanism which the initial scheme is double roll with separate function each into a single roll which combines all the functions, modifications to increase oil filtration capability and improvement sedimentation tank of the oiling machine, new cleaning procedures for oiling machine, and application of optimum parameter from DoE result. After all improvements, the overweight loss is down from 9% (baseline number) to 5.6% at the end of the research. Down 3.4% (absolute) or 37.78% (relative). The cost savings due to the reduction in overweight loss is calculated to be equivalent to IDR. 122,286,793.38 monthly.